Knowledge, Beliefs and Attitudes towards AIDS among Intermediate and Secondary School Teachers; Baghdad - Abed, *Baqir Kareem; Abdul-Rahim, Yousif; Fathalla, Mural Morad (AL-Kindy College Medical Journal, 2008)
Back ground: AIDS is considered a dreaded disease. According to recent estimates, 42 million people suffer from HIV/AIDS (90% of these being in the developing countries), with 5 million people newly infected with HIV and 3.1 million deaths in the year 2002 globally. At present, there is no effective vaccine to prevent the disease. Hence, Health education (Information, Education and Communication) activities bringing about behavioral changes in the community, promoting healthy sexual behavior and preventing the risky ones is the best possible solution to the problem of AIDS. Objectives: To find out the knowledge, beliefs and attitudes regarding various aspects of HIV/AIDS amongst intermediate and secondary school teachers in Baghdad. Methods: For this cross-sectional study, we randomly selected 48 intermediate and secondary schools covering the 6 educational directorates in Baghdad, and 642 teachers serving in these schools were selected to answer the questionnaire containing different statements concerning basic knowledge of the human immunodeficiency virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS). Results: Revealed an intermediate overall awareness about HIV/AIDS. Conclusions: Study highlights the need for teaching the proper aspects of HIV/AIDS curriculum in Iraqi schools.